2013
DOI: 10.1109/tasl.2013.2264673
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Methods for Speaker Diarization: An Integrated and Iterative Approach

Abstract: Abstract-In speaker diarization, standard approaches typically perform speaker clustering on some initial segmentation before refining the segment boundaries in a re-segmentation step to obtain a final diarization hypothesis. In this paper, we integrate an improved clustering method with an existing re-segmentation algorithm and, in iterative fashion, optimize both speaker cluster assignments and segmentation boundaries jointly. For clustering, we extend our previous research using factor analysis for speaker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
92
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(98 citation statements)
references
References 25 publications
1
92
0
1
Order By: Relevance
“…The most common approach consists of the segmentation of the input signal, followed by the merging of the segments into clusters corresponding to the individual speakers [1,2]. The alternative is to combine the segmentation and clustering steps into a single iterative process [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The most common approach consists of the segmentation of the input signal, followed by the merging of the segments into clusters corresponding to the individual speakers [1,2]. The alternative is to combine the segmentation and clustering steps into a single iterative process [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The idea of using strong prior information obtained from large datasets was further developed in studies that first adopted i-vectors as features for speaker diarization [6,7,8]. For example, [6] not only showed that diarization can be successfully carried out directly in the i-vector space, but it also achieves state-of-the-art performance on conversational telephone data from the 2008 NIST SRE corpus.…”
Section: Introductionmentioning
confidence: 99%
“…For example, [6] not only showed that diarization can be successfully carried out directly in the i-vector space, but it also achieves state-of-the-art performance on conversational telephone data from the 2008 NIST SRE corpus. Unlike [4], model selection in [8] was performed in terms of iterative variational lower bound maximization, defined for the full recording.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations